Inflammatory and immune marker trajectories from pregnancy to one-year post-birth. (January 2022) - Ross, Kharah M.; Dunkel Schetter, Christine; Carroll, Judith E.; Mancuso, Roberta A.; Breen, Elizabeth C.; Okun, Michele L.; Hobel, Calvin; Coussons-Read, Mary
Abstract: Background: Pregnancy is an immunomodulatory state, with reported systematic changes in inflammatory and immune activity by pregnancy stage. Published data are inconsistent as to how inflammatory and immune markers change and recover across pregnancy and the postpartum period, or the sociodemographic, health and pregnancy-related factors that could affect biomarker trajectories. The purpose of this study is to describe inflammatory and immune marker trajectories from pregnancy to a year post-birth, and to test associations with sociodemographic, health and pregnancy-related variables. Methods: A sample of 179 pregnant women were assessed three times during pregnancy (between 8 and 36 weeks gestation) and three times during the postpartum period (between 1 and 12 months). Maternal sociodemographic characteristics, health, and pregnancy factors were obtained at study entry. Blood samples from each assessment were assayed for interleukin(IL)-6, tumor necrosis factor(TNF)α, IL-8, IL-10, and interferon(IFN)γ. Multilevel modelling was used to characterize biomarker trajectories and associations with sociodemographic and health variables. Results: Distinct trajectories over time emerged for each biomarker. Male pregnancies were associated with higher TNFα, IL-10, and IFNγ; higher pre-pregnancy BMI was associated with higher IL-6 and IFNγ. Nulliparity was associated with greater increases in IL-6 and TNFα. Conclusions: Patterns observed for inflammatory and immune markers from pregnancy to a year postpartum support the hypothesis that the maternal immune system changes systematically across pregnancy and through an extended postpartum period. Parity, pre-pregnancy BMI and child sex are associated with inflammatory marker patterns over time. These results contribute to our understanding of how immune system activity changes from pregnancy to the post-birth period, and the factors that could affect those changes.